TOGAF-Based Business Architecture Design for FinLy in Innovation and Monetization of AI-Based Digital Financial Services - Markus Karjadi; Richardus Eko Indrajit; Erick Dazki (Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to design a business architecture for FinLy, a digital startup focused on the development and monetization of AI-based financial products. The approach follows the TOGAF Architecture Development Method (ADM), with particular emphasis on the Architecture Vision, Business Architecture, and Opportunities & Solutions phases. Employing a Design Science Research methodology, the architectural models are constructed using ArchiMate, Business Model Canvas, and Business Capability Mapping. Findings demonstrate that FinLy’s business architecture effectively maps four core capability domains to ten revenue streams that align with its digital monetization strategy. Evaluation results indicate that the architecture is modular, adaptive, and strategically aligned. The novelty of this research lies in the end-to-end integration of the TOGAF framework, generative AI technologies, and digital monetization mechanisms within the context of financial product design. As such, FinLy serves as a reference model for financial startups seeking to establish a capability-based enterprise architecture supported by cloud-native tools like Figma, Google Cloud Platform, and Oracle Database. This work contributes to the advancement of business architecture frameworks that are both technically efficient and capable of delivering personalized, adaptive, and commercially sustainable services in the digital era